Paving our ways : a history of the world's roads and pavements - Lay, M. G. (Maxwell G.); Metcalf, J. B.; Sharp, K. G. (Kieran G.) (Boca Raton : CRC Press, 2021)
"Paving Our Ways is the only comprehensive history of the world's pavements, from the earliest human settlements to the present day. It traces the human and social aspects of pavement development and use for general readers, with detailed technical background for students of transport engineering or engineering history and sociology"--
OCLC-licensed vendor bibliographic record.
Keywords: Pavements -- History; Roads -- History; TRANSPORTATION / Automotive / History; HISTORY / Civilization